The Influence Of Price, Product Quality, Promotion And Social Media On The Purchase Decision Of A3 Fresh O2 Products In Bondowoso Regency - Rolis Wikarsono (Ponpes As-Salafiyyah Asy-Syafi'iyyah, 2025)
The decline in A3 Fresh O2 product sales in Bondowoso Regency is an important background for this study. This study examines the influence of price, product quality, promotion, and social media on purchasing decisions for A3 Fresh O2 products in Bondowoso Regency. Data were collected using quantitative methods through questionnaires to 120 A3 Fresh O2 consumer respondents and analyzed using multiple linear regression with the help of SPSS. The results showed that price, product quality, and social media promotion have a positive and significant influence on purchasing decisions. Pricing that is in accordance with purchasing power and product quality, consistent product quality that meets standards, and effective promotion through social media are the main factors that determine consumer purchasing decisions. This study provides recommendations for companies to continue to maintain pricing strategies, improve product quality, and optimize social media promotions to maintain and increase sales in the local market.